Circular RNAs and Their Role in Exosomes - Han, Zeping; Chen, Huafang; Guo, Zhonghui; Shen, Jian; Luo, Wenfeng; Xie, Fangmei; Wan, Yu; Wang, Shengbo; Li, Jianhao; He, Jinhua (Frontiers in Oncology, 2022)
As a novel class of endogenous non-coding RNAs discovered in recent years, circular RNAs (circRNAs) are highly conserved and stable covalently closed ring structures with no 5′-end cap or 3′-end poly(A) tail. CircRNAs are formed by reverse splicing, mainly by means of a noose structure or intron complementary pairing. Exosomes are tiny discoid vesicles with a diameter of 40-100 nm that are secreted by cells under physiological and pathological conditions. Exosomes play an important role in cell-cell communication by carrying DNA, microRNAs, mRNAs, proteins and circRNAs. In this review, we summarize the biological functions of circRNAs and exosomes, and further reveal the potential roles of exosomal circRNAs in different diseases, providing a scientific basis for the diagnosis, treatment, and prognosis of a wide variety of diseases.